Comparison of proximal junctional kyphosis rate according to fusion level - BEZER, MURAT (ELSEVIER, 2020)
Introduction: There are two main accepted reasons of Proximal junctional kyphosis (PJK) after Scheuermann's kyphosis treatment

overcorrection of initial curve and fusion that is too short proximally. The purpose of this study was to evaluate the incidence of PJK in patients who have been previously treated for Schuermann's kyphosis with a curve exceeding 70 and corrected under 40 according to proximal fusion level T2 or T3. Methods: We retrospectively evaluated 30 patients treated for Schuermann's kyphosis with single stage posterior only procedure. We included patients that we achieved at least 50% correction of the initial curve. The surgeries were performed at the same institution by a single senior spinal surgeon. Patients were divided into two groups according to proximal fusion level T2 (16 patients) or T3 (14 patients) and evaluated for PJK, follow-ups ended three years after surgery. Results: Mean age was 22.7 in T2 and 21.6 years in T3 group. Mean preoperative Cobb angle was 78 in T2 and 78.7 in T3 group. The mean postoperative Cobb angle was 33.2 in T2 and 35 in T3 group. None of the patients showed neurologic complications. Four patients had PJK in T3 group and one needed revision. Conclusions: Selecting T2 as the proximal fusion level in Schuermann's kyphosis may decrease the incidence of PKJ. Studies with a larger number of patients needed to verify our results.
Keywords: Proximal junctional kyphosis; Fusion level; Scheuermann's kyphosis; SCHEUERMANNS KYPHOSIS; MANAGEMENT; DEFORMITY; OUTCOMES; DISEASE